HIS LEFT BUNDLE BRANCH BLOCK — PREVALENCE AND RISK FACTORS FOR ELECTRICAL AND MECHANICAL DYSSYNCHRONY - Z. I. Vozhdaeva; E. V. Sysuenkova; V. L. Glukhova; D. V. Duplyakov; S. M. Khokhlunov (Российский кардиологический журнал)
Aim. To study the risk factors of electrical and mechanical dyssynchrony development in complete left bundle branch block (CLBBB)Material and methods. In the study, we included patients with CLBBB on screening electrocardiography (ECG) and admitted consequentially to cardiologist of FSBHI SMCC FMBA of Russia. All patients underwent standard investigation that included anamnesis, physical examination, lab tests, ECG, echocardiography (EchoCG). If indicated, stress-EchoCG, coronary arteriography, magneteresonance imaging (MRI) with Gadolinium were done. Mechanical dyssynchrony was assessed at three levels: atrioventricular, interventricular, intraventricular.Results. The prevalence of novel CLBBB cases was 15,9 per 10000 ECGs, or 0,16%, among those 43,3% of patients had unsymptomatic or subclinical course. To the study we included 93 patients (49,5% were male), mean duration of QRS was 148,2±14,5 ms. Most influence on the development of electrical dyssynchrony had male gender (p=0,004), CHD in anamnesis (p=0,011), end-diastolic volume (EDV) of the left ventricle (LV) (p<0,001) and velocity of early phaseLV filling E (p=0,006). The values of mechanical dyssynchrony at atriovetricular (AVD), inter(IVD) and intraventricular (NVD) levels were 46,18±6,78%, 65,23±17,04 ms и 87,22±30,51 ms. The relation revealed, of AVD from the following variables: male gender, surface of mitral regurgitation (Smr), velocity of blood flow in early diastolic filling of the LV (E), time of isovolumic relaxation of LV. IVD was found in 87 (93,5%) patients. Development of IVD was related to female gender, age, myocardium mass index of LV (MMILV) and peak E of early filling of LV. Technical possibility of MVD with 2D-EchoCG existed just in 40% of the participants due to zones of akinesis, hypokinesis and due to difficulties of correct positioning for localization. Conclusion. CLBBB can be found on ECG of patients with a variety of cardiovascular diseases. Factors leading to electrical and mechanical dyssynchrony in CLBBB patients are seriously heterogeneous.